The effects of acute and chronic exercise on sleep. A meta-analytic review - Kubitz, K. A.; Landers, D. M.; Petruzzello, S. J.; Han, M. (Sports Medicine, 1996)
Studies attempting to ascertain the effects of acute and chronic exercise on measures of sleep have yielded conflicting results and interpretations. Methodological differences among studies may explain this lack of consensus; however, small sample sizes and subsequently low statistical power may also have contributed. In an attempt to resolve these issues, this review used meta-analytical techniques to: (a) re-examine the effects of exercise on sleep; and (b) examine possible moderators of these effects. Studies meeting the selection criteria were included in the analysis. Analyses of moderating factors were performed for stage 4 sleep and rapid eye movement (REM) sleep. The results indicated that acute and chronic exercise increased slow wave sleep (SWS) and total sleep time but decreased sleep onset latency and REM sleep. Moderating variables influencing the magnitude and direction of these effects were related to characteristics of the individual (e.g. sex, age, fitness level) and the exercise (e.g. time of day exercise was completed, type of exercise, exercise duration). Mechanisms which have been suggested to explain the relationship between exercise and sleep are discussed and directions for further research are provided.